DETERMINAN KEBAHAGIAAN PEMULUNG (STUDI KASUS DI TEMPAT PEMBUANGAN SAMPAH TERPADU PIYUNGAN) - Khoirudin, Rifki (Islamic Economics Program, Faculty of Islamic Economics and Business, 2017)
The income level can measure the individual's happiness. Indeed, one of the factors in increasing the happiness of individuals is higher income. Furthermore, this research aims to determine factors that have influenced the happiness of waste pickers who live in a giant waste landfill, Piyungan. The method uses to analyze the level of happiness is a logit model. The findings show that the female pickers feel happier than the males, the age of respondents has a negative effect, but the numbers of children and income level have positive impacts on their level of happiness. Another result indicates that the female pickers feel happier than the males